Numb chin syndrome: an ominous sign of mandibular metastasis - Razak, Abdul (BMJ Case Rep, 2018)
A 51-year-old woman a known case of stage 2 breast carcinoma in 2006 and underwent left mastectomy performed in the same year presented with bilateral lower limb pain suggestive of spinal pathology, and left chin numbness, both of 2 weeks’ duration. Examination revealed left mandibular hypoesthesia without any other sign or symptoms. Orthopantomogram was unremarkable apart from mild alveolar bone expansion at tooth 36 area, which was extracted 3 months earlier. Subsequently, a full-body positron emission tomography contrast enhanced computer tomography revealed hypermetabolic lesions of her axial (excluding skull) and appendicular skeleton. In the head and neck region, left mandibular foramen and oropharynx bilaterally showed increased metabolism suggestive of tumour metastasis. The diagnosis was numb chin syndrome secondary to mandibular metastasis. Apart from supportive treatment, she was started on palliative chemotherapy and radiotherapy. At the time of discharge, there were no active complaints other than the aforementioned hypoesthesia.